2018
DOI: 10.1007/s12031-018-1038-x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Sex Steroids Dampen Neuroinflammation and Improve Outcome of Traumatic Brain Injury in Mice

Abstract: The role of biological sex in short-term and long-term outcome after traumatic brain injury (TBI) remains controversial. The observation that exogenous female sex steroids (progesterone and estrogen) reduce brain injury coupled with a small number of clinical studies showing smaller injury in women suggest that sex steroids may play a role in outcome from TBI. We used the controlled cortical impact (CCI) model of TBI in mice to test the hypothesis that after CCI, female mice would demonstrate less injury than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Taking functional and molecular findings together, the protective effect of estrogen‐specific expression of NKRs in baroreflex afferent pathway could be pinpointed. Consistently, recent animal study showing that intact female mice have a significant lesser damage after traumatic brain injury compared with male and OVX mice and the outcomes of OVX mice recover dramatically with estrogen treatment, suggesting a potential key role of estrogen‐dependent NKRs expression in the protection against neuroinflammation by down‐regulation of SP‐mediated cardiovascular responses, which further explains why the sensitivity to traumatic brain injury and caused brain damage are far less in females.…”
Section: Discussionsupporting
confidence: 62%
“…Taking functional and molecular findings together, the protective effect of estrogen‐specific expression of NKRs in baroreflex afferent pathway could be pinpointed. Consistently, recent animal study showing that intact female mice have a significant lesser damage after traumatic brain injury compared with male and OVX mice and the outcomes of OVX mice recover dramatically with estrogen treatment, suggesting a potential key role of estrogen‐dependent NKRs expression in the protection against neuroinflammation by down‐regulation of SP‐mediated cardiovascular responses, which further explains why the sensitivity to traumatic brain injury and caused brain damage are far less in females.…”
Section: Discussionsupporting
confidence: 62%
“…In healthy animals we find no effects of biological sex on glymphatic influx across anesthesia, the day, and in aging. This was unexpected because we know sex affects common disorders, such as cardiovascular disease prevalence 10 , Alzheimer’s disease 11 , 13 , 36 , and recovery from traumatic brain injury 15 17 , which generally correlate to glymphatic dysfunction. The observations reported here suggest it is not underlying male/female differences in glymphatic function that drive disease, but rather differences in homeostatic responses to disease that lead to male/female differences in pathology, prevalence, and long-term recovery.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be caused by underlying differences in genetic susceptibility, and lifestyle resilience between men and women 13 . Additionally, there is some evidence in humans 14 and from rodent models that male and female animals recover differently after traumatic brain injury, with female mice having reduced neuroinflammation 15 , 16 and male mice having increased angiogenesis a week after injury 17 . How sex may affect the glymphatic system, which is impaired in aging 18 , neurodegenerative disease models 19 22 and traumatic brain injury 21 , 23 , remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…26 In contrast, more recent studies have demonstrated significant sex differences in microglial and astrocyte activation during acute phase responses after moderate-severe TBI. 25,28,29 Nevertheless, all studies to date have used immunohistochemical assessments that provide excellent spatial and morphological resolution of post-traumatic neuroinflammation, but are limited in their ability to provide phenotypic and functional assessments of immune cell function in either resident (microglia) or infiltrating (myeloid, lymphocytes) cells in the central nervous system (CNS). Flow cytometry approaches can distinguish microglia from infiltrating myeloid cells in the brain based on the relative expression of the CD45 antigen, and provide the added advantage of assessing functional responses ex vivo.…”
Section: Introductionmentioning
confidence: 99%